Study Morfologi dan Marfometri Das Way Mesuji - Danang Primanggara; Suprapto Suprapto (Jurnal Ilmiah Teknik Pertanian - TekTan, 2014)
Morphology and Morphometry watershed is a specific description of the watershed that was characterized by parameters related with: broad, shape, orientation, altitude, slope, flow patterns, river gradient, and the River’s density. This study aims to obtain data Morphology and Morphometry watershed conditions. Steps of this study were (1) identified criteria of morphology and morphometry watershed, (2) overlay watershed parameters. The results of this study were (1) Way Mesuji sub watershed is dominated by an elongated shape. This is caused the value of each Circularity Ratio Way Mesuji sub-watershed  less than 0.5; (2) Sub-watershed Slope is dominated by flat and ramps.This will result a slow velocity river stream; (3) region  altitude was dominated by a height of 25 meters above sea leve; (4) The flow pattern was dominated by the denditrik flow pattern; (5) The gradient of the river was dominated  less than 1%. Its caused that  river flow velocity will be low; (6) river density was dominated by medium and low grade.This shows that this area enough water reserves. Keywords: morphology, morphometry, Way Mesuji watershed.